Individual and structural correlates of willingness for intravenous buprenorphine treatment among people who inject sublingual buprenorphine in France - Salim Mezaache; Patrizia Carrieri; Laélia Briand-Madrid; Virginie Laporte; Alain Morel; Daniela Rojas Castro; Perrine Roux (BMC, 2021)
Abstract Background Some people do not benefit from oral administration of opioid agonist treatment, and an intravenous (IV) formulation may be more suitable. Our objective was to evaluate the willingness of people who regularly inject sublingual buprenorphine to receive IV buprenorphine as a prescribed treatment, and to examine related correlates. Methods We performed a secondary analysis of data from the cross-sectional study PrebupIV, conducted in France in 2015 among 557 people who inject opioids. The study comprised questionnaires completed either face to face or online and community-based workshops. We only included participants who reported buprenorphine as their main injected drug (n = 209). Willingness to receive IV buprenorphine treatment was measured on a scale from 0 to 10. Ordinal logistic regression identified correlates of willingness. Artworks and testimonies from participants in the workshops were also used to illustrate correlates of willingness. Results Among the 209 participants, the mean score (SD) for willingness to receive IV buprenorphine was 8.0 (2.8). Multivariate analysis showed that participants who reported using non-prescribed buprenorphine (AOR = 4.82, p = 0.019), a higher daily dosage of buprenorphine (AOR (for 1 mg) = 1.05, p = 0.043), and a higher number of complications due to injection (AOR = 2.28, p = 0.037), were more willing to receive IV buprenorphine treatment. Conclusions Willingness to initiate IV buprenorphine treatment was high among people who regularly inject sublingual buprenorphine. A prescribed IV formulation could attract and retain more people into care and reduce harms associated with the injection of buprenorphine tablets.